Subjective well-being evalution in adolescents: Relationships with sex and age - Silva, Doralúcia Gil da (2018)
Adolescents wellbeing study is justified by the importance of promotion of positive aspects in this period of development. Gender and age are associated to variation in life satisfaction and positive and negative affects. This work has the objective to evaluate the level of adolescents’ wellbeing, from a index which agrupate positive and negative affects and life satisfaction, observing gender and age group. A Multidimensional Scale of Life Satisfaction and a Positive and Negative Affect Scale were applied collectively in 426 adolescents (M=14.91 years old; SD=1.65) from public schools of Porto Alegre. Results pointed highest average between boys in family satisfaction, self-efficacy and well-being. Girls presented more friendship satisfaction, more negative affect and less life satisfaction. These data indicate the need of interventions that promote positive aspects between girls.